HUBUNGAN REWARD DAN IKLIM KERJA DENGAN EFEKTIVITAS TIM KERJA GURU SMP NEGERI DI KECAMATAN BEKASI UTARA KOTA BEKASI - Dini Wiandini (Jurnal Manajemen Pendidikan, 2012)
The objective of this research is to know the relationship of reward and work climate with teacher work team effectiveness of State Junior High School in sub district of North Bekasi at the district of Bekasi.The research is done to the teachers of State Junior High School in the sub district of North Bekasi at the District of Bekasi by using the survey method. Framed population of this research are 225 teachers. Based on Slovin’s formula, there are 144 samples which are taken by combining the Random Sampling,Proportional Sampling, and Area Sampling. The data of each variable are gotten by instrument namely questionare. It is processed by the regression and correlation analytical technique to describe the correlation among the variables.The result of this research concludes that there are positive relationship between (1) reward with team effectiveness, (2) work climate with team effevtiveness, and (3) reward and work climate as together with team effectiveness.